A Bayesian inversion of TROPOMI methane observations over South Africa: Implications for bottom-up inventories - Keneuoe A. Maliehe; James Goulding; Stuart Marsh; Mohammed S. Alam (Science of The Total Environment, 2026)

A standard for geological evaluation of urban underground space resources in the Beijing plain - Han-han He; Cheng-shan Wang; Jing He; Yuan-xin Zhou; Lei Wang; Stuart Marsh; Chao Li; Tong-ming Fang; Fang-zhen Li; Sheng-li Cao; Jing Liu; Yi-ting Zhao (Bulletin of Engineering Geology and the Environment, 2025)

Linking geo-models for geomorphological classification using knowledge graphs - Yanmin Qi; Yunqiang Zhu; Shu Wang; Yutao Zhong; Stuart Marsh; Amin Farjudian; Heshan Du (Computers & Geosciences, 2025)

New Zealand Myrtaceae are susceptible to a strain from the Eucalyptus biotype of Austropuccinia psidii present in South America - Julia Soewarto; Carlos Pérez; Michael Bartlett; Chanatda Somchit; Beccy Ganley; Roanne Sutherland; Sofía Simeto; Jane E. Stewart; Jorge R. Ibarra Caballero; Stuart Fraser; Peter M. Scott; Jayanthi Nadarajan; et al. (Biological Invasions, 2025)
The international spread of the myrtle rust pathogen, Austropuccinia psidii , can be largely attributed to the “pandemic” biotype that has more than 450 host species. However, within South America, the putative native range of A. psidii , multiple biotypes have been characterised, each with a restricted known number of hosts. These biotypes may pose a significant biosecurity threat to countries already affected by the pandemic biotype. Here, we report the susceptibility of four species of Myrtaceae from New Zealand, pōhutukawa ( Metrosideros excelsa ), mānuka ( Leptospermum scoparium ), kānuka ( Kunzea ericoides ), and rawiri mānuka ( Kunzea ericoides ‘gumland ecotype’), to a strain of the Eucalyptus biotype of A. psidii . Symptoms and signs developed on inoculated plants of all species. Qualitative resistance phenotypes, with no disease development, were observed for all four species. However, no hypersensitive responses were observed. As seen for other biotypes, pōhutukawa had the greatest susceptibility, while kānuka had the lowest. These findings are consistent with prior work, showing that the Eucalyptus biotype can infect a broader range of species than its field host association implies. As well as uredinia (asexual spores), telia (sexual spores) developed on several plants, indicating that these species could provide a universal host for sexual reproduction and outcrossing between biotypes. Knowledge that the Eucalyptus biotype of A. psidii is virulent on several indigenous New Zealand Myrtaceae will inform future biosecurity risk assessments. These findings highlight the need to develop diagnostics tools to differentiate between biotypes and allow rapid responses to potential future incursions.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Vegetation productivity responses to drought on tribal lands in the four corners region of the Southwest USA - Mohamed Abd Salam El-Vilaly; Kamel Didan; Stuart E. Marsh; Willem J. D. van Leeuwen; Michael A. Crimmins; Armando Barreto Munoz (Frontiers of Earth Science, 2018)

Large-scale forcing of the European Slope Current and associated inflows to the North Sea - Robert Marsh; Ivan D. Haigh; Stuart A. Cunningham; Mark E. Inall; Marie Porter; Ben I. Moat (Ocean Science, 2017)
The European Slope Current provides a shelf-edge conduit for Atlantic Water, a substantial fraction of which is destined for the northern North Sea, with implications for regional hydrography and ecosystems. Drifters drogued at 50 m in the European Slope Current at the Hebridean shelf break follow a wide range of pathways, indicating highly variable Atlantic inflow to the North Sea. Slope Current pathways, timescales and transports over 1988–2007 are further quantified in an eddy-resolving ocean model hindcast. Particle trajectories calculated with model currents indicate that Slope Current water is largely recruited from the eastern subpolar North Atlantic. Observations of absolute dynamic topography and climatological density support theoretical expectations that Slope Current transport is to first order associated with meridional density gradients in the eastern subpolar gyre, which support a geostrophic inflow towards the slope. In the model hindcast, Slope Current transport variability is dominated by abrupt 25–50 % reductions of these density gradients over 1996–1998. Concurrent changes in wind forcing, expressed in terms of density gradients, act in the same sense to reduce Slope Current transport. This indicates that coordinated regional changes of buoyancy and wind forcing acted together to reduce Slope Current transport during the 1990s. Particle trajectories further show that 10–40 % of Slope Current water is destined for the northern North Sea within 6 months of passing to the west of Scotland, with a general decline in this percentage over 1988–2007. Salinities in the Slope Current correspondingly decreased, evidenced in ocean analysis data. Further to the north, in the Atlantic Water conveyed by the Slope Current through the Faroe–Shetland Channel (FSC), salinity is observed to increase over this period while declining in the hindcast. The observed trend may have broadly compensated for a decline in the Atlantic inflow, limiting salinity changes in the northern North Sea during this period. Proxies for both Slope Current transport and Atlantic inflow to the North Sea are sought in sea level height differences across the FSC and between Shetland and the Scottish mainland (Wick). Variability of Slope Current transport on a wide range of timescales, from seasonal to multi-decadal, is implicit in sea level differences between Lerwick (Shetland) and Tórshavn (Faroes), in both tide gauge records from 1957 and a longer model hindcast spanning 1958–2012. Wick–Lerwick sea level differences in tide gauge records from 1965 indicate considerable decadal variability in the Fair Isle Current transport that dominates Atlantic inflow to the northwest North Sea, while sea level differences in the hindcast are dominated by strong seasonal variability. Uncertainties in the Wick tide gauge record limit confidence in this proxy.

Contemporary and historical classification of crop types in Arizona - Kyle A. Hartfield; Stuart E. Marsh; Christa D. Kirk; Yves Carrière (International Journal of Remote Sensing, 2013)

Identification of materials related to acid mine drainage using multi-source spectra at S. Domingos Mine, southeast Portugal - Lídia Quental; António Jorge Sousa; Stuart Marsh; Maria Manuela Abreu (International Journal of Remote Sensing, 2013)

Evaluating Post-wildfire Vegetation Regeneration as a Response to Multiple Environmental Determinants - Grant M. Casady; Willem J. D. van Leeuwen; Stuart E. Marsh (Environmental Modeling & Assessment, 2010)

A Landscape Approach for Detecting and Evaluating Change in a Semi-Arid Environment - William G. Kepner; Christopher J. Watts; Curtis M. Edmonds; John K. Maingi; Stuart E. Marsh; Gonzalo Luna (Environmental Monitoring and Assessment, 2000)

Characterizing mixing in a rotating drum bioreactor for solid-state fermentation - A.J. Marsh; D.M. Stuart; D.A. Mitchell; T. Howes (Biotechnology Letters, 2000)

O2 uptake during solid-state fermentation in a rotating drum bioreactor - Anna J. Marsh; David A. Mitchell; Deidre M. Stuart; Tony Howes (Biotechnology Letters, 1998)